A Comparative Study Between Conventional ICP-OES and the Innovative PLS Model-Assisted ICP-OES for the Assay of Trace Elements. (8th July 2020) - Michael, Adel M; Mohamed, Ahmed A; Abdelaziz, Yousef A; Fahmy, Nesma M
Abstract: Background: Inductively coupled plasma is widely used for elemental analysis with the advantage of being eco-friendly since the discharge is free of contaminants. Objective: A rapid, novel method was developed for the quantitation of trace elements using inductively coupled plasma with optical emission spectrometry.This method has the advantage of simultaneous calibration compared to the conventional method. Method: The assay was carried out for iron, copper, zinc, and molybdenum using the linear regression model partial least-squares. Results: The method was optimized and validated as per the International Conference on Harmonization guidelines, showing highly accurate and precise results. The linearity range was 0.25–4 ppm for all trace elements under investigation. The method was applied for the assay of the cited elements in non-chelated and amino acid chelated multi-mineral preparations in the Egyptian market with acceptable mean percent recovery. Conclusions: In comparison with the official method by flame emission, statistical analysis showed no significant difference with Student's t -test and F -values. Highlights: Inductively coupled plasma is superior as all of the elements can be measured simultaneously. The method was found to have a high degree of specificity and can be easily applied in routine elemental analysis in laboratories.